K-State First: A Proposal to Create a First-Year Program at Kansas State University - Kansas State University, K-State First (Kansas State University. K-State First., 2009)
A proposal to start a first-year student experience program at Kansas State University. The report provides an outline of recommendations for the implementation of the program, research regarding first-year retention and graduation rates, a summary of the proposal, and a future vision.
Keywords: First-year experience program; Reports; Proposal; Retention; Papers (document genres)